2011
DOI: 10.1128/iai.00922-10
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T Cells Are Not Essential for Control of Early AcuteCryptosporidium parvumInfection in Neonatal Mice

Abstract: Cryptosporidiosis is an important diarrheal disease of humans and neonatal livestock caused by؊/؊ mice around the peak of infection, but IL-10 expression was also higher in WT mice. These results suggest that although CD4 ؉ T cells may be important for elimination of C. parvum, these cells are dispensable for controlling the early acute phase of infection in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
(43 reference statements)
1
23
1
Order By: Relevance
“…A number of findings, however, cast uncertainty on a major protective function of T cells in the newborn mouse. For example, no increases in the percentages of CD4 + or CD8 + T cells in the Peyer's patches or lamina propria were observed during infection . No antigen‐specific activation of T cells was obtained in splenocytes taken from neonatal mice at different times during the patent infection period .…”
Section: Infections In Immunocompromised and Neonatal Micementioning
confidence: 99%
See 1 more Smart Citation
“…A number of findings, however, cast uncertainty on a major protective function of T cells in the newborn mouse. For example, no increases in the percentages of CD4 + or CD8 + T cells in the Peyer's patches or lamina propria were observed during infection . No antigen‐specific activation of T cells was obtained in splenocytes taken from neonatal mice at different times during the patent infection period .…”
Section: Infections In Immunocompromised and Neonatal Micementioning
confidence: 99%
“…In addition, similar acute patterns of infection were observed in neonatal C57BL/6 wild type and Rag2 −/− mice. When adult wild type and Rag2 −/− mice previously infected as neonates were treated with an immunosuppressive drug, however, relapse of infection was observed only in Rag2 −/− mice . Even without treatment, relapse of infection that became fatal eventually occurred in most Rag2 −/− mice.…”
Section: Infections In Immunocompromised and Neonatal Micementioning
confidence: 99%
“…Because of the ‘minimally invasive’ nature of Cryptosporidium infection, mucosal epithelial cells are critical to the host’s anti- Cryptosporidium immunity. Indeed, a recent study with newborn mice showed similar acute patterns of C. parvum infection in C57BL/6 wild-type and T and B cell-deficient Rag2 −/− mice (Korbel et al 2011). Upon Crypto-sporidium infection, epithelial cells quickly initiate a series of innate immune reactions, including production of antimicrobial peptides (e.g.…”
Section: Mucosal Epithelial Cells Are Critical Players In the Host’s mentioning
confidence: 95%
“…They are activated by IL-15 secreted by IECs, and have been shown to lyse C. parvum -infected IECs in response to IL-15 in vitro (62). Previous studies found that mice lacking functional NK cells were more susceptible to Cryptosporidium infection (63,64), while treatment of immunocompetent and immunodeficient mice with IL-12, a potent NK cell activator, enhanced protection (65). Both studies found that NK cell-dependent protection was primarily mediated through IFN-γ.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 99%